Study of Slums on Jalan Sultan Hasanuddin RT 002/RW 010, Batu Merah Bawah Village, Ambon City - Toatubun, Damiana; Lasaiba, Mohammad Amin; Sihasale, Daniel Antoni (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Slums are characterized by high population density and inadequate housing. Homeownership is a crucial factor influencing slum settlements. This research focuses on slum settlements on Sultan Hasanuddin Street, Batu Merah Bawah Village, Ambon City. It employs a qualitative approach to gain an in-depth understanding of the characteristics of the slum settlement and relevant social and economic factors. The research findings reveal that the surveyed community faces social and economic challenges, with most households having low monthly incomes, indicating income inequality. While most respondents consider their income sufficient, 20% still struggle economically. Additionally, attention is drawn to the urgent need for housing and basic infrastructure improvements, such as primitive roads and limited sanitation facilities. Diversity in family structures, homeownership, and access to clean water highlight the necessity of inclusive policies for essential services like sanitation, electricity, and clean water. These findings serve as a foundation for better economic development, housing, and infrastructure initiatives to enhance overall quality of life and community welfare.